On Certain Linear Structures of Bounded Vector - Valued Sequence Space on Product Normed Space - Pahari, Narayan` Prasad (Journal of Advanced College of Engineering and Management, 2016)
Available with full text. Journal of Advanced College of Engineering and Management, Vol. 2, 2016, Page: 31-39